Analisis Kepuasan Pengguna Aplikasi Halodoc Dengan Menggunakan Metode Usability Testing (Studi Kasus: Klinik Nayaka Era Husada 01 dan 02 Basuki Rahmat Palembang) - Jimmi; Linda Atika (Teknik Komputer Politeknik Negeri Sriwijaya, 2023)
This study aims to determine the satisfaction of users of the Halodoc application by using the usability testing method. The type of data in this study is quantitative. Sampling technique in this study using purposive sampling. The data collection in this study was carried out directly, namely by means of a direct survey using google form (online) by measuring the Likert scale variable. Based on the results of multiple regression analysis, the variables that have an influence on the real condition of information users are the variables learnbility (X1), Efficiency (X2) Memorability (X3) Errors (X4), and Satisfaction (X5) have a significant influence on user satisfaction, Based on the analysis correlation coefficient relationship using SPSS is 63,812. based on the results of Fcount obtained 12.798 > Ftable 2.47, so it can be concluded that there is a relationship between X1, X2, X3, X4, and X5 together with Y. Based on the R Square value of 0.405, there is a relationship between usability testing variables and user satisfaction is 40.5% while the remaining 59.5% is influenced by other variables.